Equal Segmentation based Approximate Adder Design for High Speed Operations (Indo-American Journal of Life Sciences and Biotechnology, 2022)
It's not always necessary to get the most accurate results in many cases, such as in image andmultimedia data processing, artificial intelligence, and machine learning. As a result, approximationcomputing has been developed. Using approximation computing makes a big impact in terms of theamount of space, latency, and power used. It may not be the best choice for error-resistant applicationssince its ED is too high; and Error also rises as bandwidth increases. This research introduced a novelstrategy that is equally segmented in order to enhance these parameters. Using this technique, an N-bitadder is broken down into equal-sized and accurate sub-adders. Segment size (k) is one of two factorsused to build an N-bit ESA. Carry propagation length and Overlapping bits are two examples of this. It'sthe bare minimum in terms of carry prediction bits. So the best configurations differ depending on theESA adder design. Three kinds of adder architectures are included in our analysis: those with smallerarea; those with smaller delay; and those with an in-between delay and area size.